Wine traditions in literature of Lubusz Land in the context of the regional policy of place - Kamila Gieba (In Gremium. Studies in History, Culture and Politics, 2019)
The article concerns motif of wine in postwar literature about the Lububsz Land and regional politics of place and politics of memory. The politics concenrs three aspects of local imaginary geography: arcadia, Piast;s myth and multicultiralism of borderlines. The research materials are selected poetry, fairy tales and novels about the Lubusz Land.